Fighting locusts with fungi - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A major research programme to develop fungi as biological pesticides is under way at CAB International's Institute of Biological Control. A total of UKL25 million is being provided by the Canadian International Development Agency (CIDA), the...